Finite Element Model Optimization Using Diagonal Mass Matrix - B.P. Wang; F.H. Chu (Shock and Vibration)
By adjusting the analytic mass matrix or stiffness parameters, the correlation between measured and computed modal data can be improved. This article proposes a simple method for model optimization. Numerical examples will be included to illustrate the proposed approach.